Goetz: Textbook of Clinical Neurology, 2nd ed. - CHRISTOPHER G. GOETZ, MD (2003)
The first edition of Textbook of Clinical Neurology, published in 1999, was envisioned to answer an educational need not met by other textbooks. My original co-editor and I modeled the text after the three-part process used by clinical neurologists to diagnose and treat patients with neurological illnesses: establishing anatomical localization and definition of clinical syndromes based on the neurological examination and history (Part One), using diagnostic tools to clarify the syndromic diagnosis (Part Two), and explaining etiologies of neurological illnesses to establish the cause of neurological disorders (Part Three). In clinical practice, this three-step system is used in everyday diagnosis and treatment. In both the first and second editions, a clear and consistent format guides readers through this sequence.